DIPLOMASI BUDAYA INDONESIA MELALUI INTERNATIONAL GAMELAN FESTIVAL 2018 - Afrianda, Tio; Iskandar, Irwan (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2023)
This research delves into the execution of Indonesian Cultural Diplomacy through the platform of the International Gamelan Festival 2018 hosted in Solo. The orchestration of this event was overseen by the Indonesian government with the aim of cultivating a positive worldwide viewpoint of the country. The central emphasis of this investigation centers on dissecting Indonesia's showcasing of the cultural diplomacy principles of Transmission, Acceptance, and Coexistence, all encapsulated within the context of the International Gamelan Festival 2018. This process significantly contributed to the shaping of Indonesia's global image. The primary beneficiaries of this Indonesian cultural diplomacy venture were the international participants actively involved in the festival. The research methodology employed for this study is descriptive in nature, involving an in-depth examination of relevant literature to gather data. This investigation is rooted in both the principles of cultural diplomacy theory and a pluralistic perspective. These conceptual frameworks serve as foundational guides for analyzing Indonesia's strategic approach to cultural diplomacy, as demonstrated by its involvement in the International Gamelan Festival. The outcomes derived from this study highlight that the Indonesian cultural diplomacy, as showcased through the International Gamelan Festival 2018 in Solo, substantially amplified Indonesia's positive global reputation. This impact was particularly evident among international participants who deeply engaged with the festival's cultural presentations. Furthermore, this diplomatic endeavor facilitated the dissemination of insights into Indonesian culture and cultivated a sense of familiarity among the foreign attendees actively participating in the International Gamelan Festival 2018 in Solo. Keyword: International Gamelan Festival, culture, diplomacy